Regeneration of tree tomato plants (Cyphomandra betacea Cav. Sendt.) induced by organogenesis from callus - Apraez M, José Julián; Romo D, Janio Fabián; Lagos B., Tulio Cesar (Revista de Ciencias Agrícolas, 2013)
The aim of this study was to obtain tree tomato plants (C. betacea) in vitro, by induced organogenesis in callus. A complete randomized block design, with four treatments and four replications was used. Treatments studied were: (1) MS (check), (2) MS + 2.4D 5μM, (3) MS + 2.4D 10μM y (4) MS + 2.4 D 15μM; 13μM of kinetin were added to treatments 2, 3, and 4. The experimental unit consisted of 10 glass containers, with a capacity of 120 ml. In each container 20 mi of culture medium were added and were sown three calluses with a diameter of 5 mm. The highest percentage of regenerated plants (14,66%) was obtained with treatment MS + 2,4 D 5μM (T2), and the lowest (2,91%) with MS + 2,4D 15μM. Formation of roots, stems, leaves and regenerated plants was higher using MS + 2.4D 5μM (T2), with values of 0,52, 0,14, 0,15 and 0,05, respectively, while lower values were obtained with treatment 4, MS + 2.4 15μM, with of values 0,09, 0,04, 0,008 and 0, for the same characteristics.